On $k$-Fibonacci balancing and $k$-Fibonacci Lucas-balancing numbers - Rihane, S.E. (Carpathian Mathematical Publications, 2021)
The balancing number $n$ and the balancer $r$ are solution of the Diophantine equation $$1+2+…+(n-1) = (n+1)+(n+2)+…+(n+r). $$ It is well known that if $n$ is balancing number, then $8n^2 + 1$ is a perfect square and its positive square root is called a Lucas-balancing number. For an integer $k≥ 2$, let $(F_n^{(k)})_n$ be the $k$-generalized Fibonacci sequence which starts with $0,…,0,1,1$ ($k$ terms) and each term afterwards is the sum of the $k$ preceding terms. The purpose of this paper is to show that 1, 6930 are the only balancing numbers and 1, 3 are the only Lucas-balancing numbers which are a term of $k$-generalized Fibonacci sequence. This generalizes the result from [Fibonacci Quart. 2004, 42 (4), 330-340].